Multiple Level Crowding: Crowding at the Object Parts Level and at the Object Configural level. (November 2015) - Kimchi, Ruth; Pirkner, Yossef
In crowding, identification of a peripheral target in the presence of nearby flankers is worse than when the target appears alone. Prevailing theories hold that crowding occurs because of integration or "pooling" of low-level features at a single, relatively early stage of visual processing. Recent studies suggest that crowding can occur also between high-level object representations. The most relevant findings come from studies with faces and may be specific to faces. We examined whether crowding can occur at the object configural level in addition to part-level crowding, using nonface objects. Target (a disconnected square or diamond made of four elements) identification was measured at varying eccentricities. The flankers were similar either to the target parts or to the target configuration. The results showed crowding in both cases: Flankers interfered with target identification such that identification accuracy decreased with an increase in eccentricity, and no interference was observed at the fovea. Crowding by object parts, however, was weaker and had smaller spatial extent than crowding by object configurations; we related this finding to the relationship between crowding and perceptual organization. These results provide strong evidence that crowding occurs not only between object parts but also between configural representations of objects.